THE SUBLETHAL DISRUPTING EFFECTS OF FLUOXETINE-HCI (FLX) ON CATALASE (CAT) ACTIVITY AND MALONDIALDEHYDE (MDA) LEVELS IN ZEBRAFISH, DANIO RERIO - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
The aim of this study is to investigate sub-lethal disrupting effects of fluoxetine-HCl (FLX) on catalase (CAT) activity and malondialdehyde (MDA) levels of liver tissue and whole body in zebrafish (Danio rerio). FLX is the active compound of the antidepressant Prozac(TM) and acts as a selective serotonin reuptake inhibitor (SSRI) in humans. Zebrafish are well-characterized model organism especially for the antioxidant enzyme activities for humans. Our study was planned as a model to investigate the effects of daily intake doses of FLX, which adapted from human proportionally to weight, on liver tissue of zebrafish. CAT, MDA and total protein levels were detected using spectrophotometric methods. The six experiment study groups were composed as; 150 ng fluoxetine-HCl exposed to each aquarium tank and five zebrafish were studied at 15 min., 30 min., 60 min., 4 days and 8 days of exposure and the last group was composed as the control group. In our study, it is determined that the activity of CAT increases in two experimental group after exposure FLX (15 min. and 30 min.) in liver tissue. Following one hour FLX treatment, it was observed that CAT activity decreased, whereas after four days treatment it was re-increased. Once for all, following 8 days treatment of FLX, it was observed that CAT activity significantly decreased. Likewise we found that the MDA levels decreases in all experimental groups after exposure FLX in liver tissue definitely. In whole body groups, MDA levels was firstly decreased after exposure FLX but MDA levels was increased subsequently compared to the control group in this study. In conclusion, building on the framework surrounding drug metabolism in fish, it is apparent that the capacity of fish liver to metabolize FLX in vitro is variable.
Keywords: Fluoxetine-HCl; oxidative stress; zebrafish; FISH; EXPOSURE; ANTIDEPRESSANTS; PHARMACEUTICALS; SEROTONIN; PRODUCTS; EFFLUENT; BEHAVIOR; LARVAE